2020
DOI: 10.3390/foods9040426
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Meal and Snacking Behaviour of Older Adults in Australia and China

Abstract: Sensory perception and food preferences change as we age. This paper encompassed two studies with the aim being to investigate meal and snacking behaviour of older adults towards food, especially meat products, and understand the desirable characteristics of those products. A qualitative multivariate analysis (QMA) focus group with Australian and Chinese older (60–81 years old) adults was conducted. A conjoint concept database was used to determine older consumers’ wants and needs for food in Australia and Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Hence, in contrast to our previous study [21], we achieved tender meat with lower cooking time of 8 h, with the use of GP-injection. However, the soft texture or over-tenderisation may be suitable for some specialised markets, for instance, the elderly population [50]. There are papers showing that people vary in their liking for tenderness and texture of the meat [47].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in contrast to our previous study [21], we achieved tender meat with lower cooking time of 8 h, with the use of GP-injection. However, the soft texture or over-tenderisation may be suitable for some specialised markets, for instance, the elderly population [50]. There are papers showing that people vary in their liking for tenderness and texture of the meat [47].…”
Section: Discussionmentioning
confidence: 99%
“…The “part worth utility value” is the regression coefficient for that particular attribute or the “level” that the attribute increases. or decreases the overall score [ 72 ]. In the regression modeling based on a dummy variables process, each individual “attribute” is included as a component in the model; the overall category is not part of the model.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in the case of unnecessary snacking, a non-habitual snacker lacks a biological motivation for eating snack foods, therefore snacking without hunger will elevate the amount of energy consumed, which can result in consequent weight gain [32,33]. Using a qualitative multivariate analysis (QMA) map, researchers investigated the snacking behavior of adults towards food from Australia and China and found that sweet biscuits were ranked as likely to eat everyday [34]. A study determined how often Swiss respondents usually ate breakfast [35].…”
Section: Motives For Eating Spbs: Environmental and Physical Eatingmentioning
confidence: 99%